PRODUÇÃO, PURIFICAÇÃO PARCIAL E CARACTERIZAÇÃO BIOQUÍMICA DE GLUCOAMILASE DE Aspergillus niger OBTIDA POR FERMENTAÇÃO EM ESTADO SÓLIDO - Slivinski, Christiane Trevisan (2007)
Glucoamylase is one of main enzymes responsible for the hydrolysis of starch to form the glucose syrup, raw material used by the food industry for the production of cool drinks, ice creams, sauces, breads and as carbon source in fermentations. The enzyme is normally produced by filamentous fungi. In the present work glucoamylase was produced by Aspergillus niger through solid-state fermentation, using the industrial waste of potato processing, during a period of 48 h at 32 ºC. The biochemical characterization of the rude enzymatic preparation showed as the optimum performance pH band near 5,0 and as the optimum temperature 60 ºC, with an average activity of 11,87 U/mL. After 26 hours of incubation of this preparation, the glucoamylase kept 58,75 % (9,70 U/mL) and 60,33 % (9,96 U/mL) of its activity at 35 and 60 ºC respectively; after 28 hours of incubation in pH 4,6, it kept 72,87 % (8,88 U/mL) of residual activity. The kinetic parameters for the hydrolysis of soluble starch were Km = 1,68 mg/mL and Vmáx = 41,15 U/mL. The enzyme was partially purified through i) precipitation with ammonium sulphate between 60-85 % of saturation ii) anion-exchange chromatography in Q-Sepharose and iii) gel filtration chromatography in Sephadex G-100, with a purification factor of 109,23 fold and a yield of 11,71 %. The eletrophoretic analyses demonstrated that the studied glucoamylase presents molar mass around 130,88 kDa. After submitted to the purification steps, the enzyme kept the same optimum conditions of pH and temperature of the raw preparation, with 152,85 U/mL of average activity. With regard to stability, after 4 hours of incubation in pH 5,0, the glucoamylase presented 83 % (124,99 U/mL) of residual enzymatic activity, whereas after 8 hours only 22,72 % (34,22 U/mL) remained. Concerning temperatures, greater stability was observed at 35 and 15 ºC, in which after 24 hours of incubation 87 % (131,14 U/mL) and 85 % (127,77 U/mL) of the catalytic capacity remained, respectively. The values of Km and Vmáx for the partially purified glucoamylase were 0,049 mg/mL and 163,93 U/mL.